Coproduction to improve preventive health services—experiences from Germany. (11th December 2021) - Abu-Omar, Karim; Weissenfels, Anja; Mino, Eriselda; Naber, Inga; Klamroth, Sarah; Geidl, Wolfgang; Pfeifer, Klaus
Summary: Due to the beneficial impact of regular physical activity (PA) on non-communicable diseases, the number of countries integrating exercise referral schemes (ERSs) into their healthcare systems is growing. Owing to the limitations of existing PA promotion concepts in Germany's healthcare system, efforts are currently being made towards developing a nationwide referral pathway. A research group at the Friedrich-Alexander-University Erlangen-Nürnberg is coordinating these efforts within a project funded by the Federal Ministry of Health. The aim is to develop, implement and evaluate a regional-level ERS that has the potential to be scaled up across Germany in the event of its demonstrated effectiveness. The project is based on an adapted Cooperative Planning approach requiring interaction between the academic sector and different actors of the healthcare sector. The present commentary reflects on challenges faced in the early stages of the co-production process. Besides the development of an adequate co-production methodology, it critically discusses stakeholder participation, knowledge gaps and actors' willingness to take responsibility. In addition, although patients are represented by dedicated organizations, their perspective cannot be adequately captured using a co-production approach. Despite the joint development of an ERS, there remain important questions regarding the appropriateness of the co-production approach in a healthcare setting. Lay Summary: Regular physical activity (PA) reduces one's risk of developing various diseases and also plays a favourable role in managing symptoms and preventing further complications. Nationally and internationally, there exist different concepts on how to increase PA in the population at large. The Friedrich-Alexander-University Erlangen-Nürnberg is currently working on a project that focuses on promoting PA in primary care. This project involves collaboration among various actors in the German healthcare system, such as healthcare insurances, representatives of physicians, patients and exercise specialists, who represent different interests and are experts in their fields of knowledge. During this process, various barriers have come to light, which yield important lessons for further studies. For example, there are differences in actors' levels of knowledge of the healthcare system and their willingness to take responsibility and initiative in the collaborative process. This article should give an impression of the joint development of exercise referral schemes, show the strengths and weaknesses and encourage exchanges of similar experiences of co-production processes.